Role Conflicts in Jordan family during Covid- 19 pandemic and its relation with familial violence patterns - Al-Alotoum, Bakr Mustafa; Al-Sarayrah, Wala AbdulFattah (Journal of Humanities & Social Sciences, 2022)
This study aimed to know the reality of the Jordanian family in the northen region during the Corona pandemic, in terms of: knowing the new roles and their level that were produced by the Corona pandemic, and then negative effects it caused, around the form of the family relationship between spouses, in addition to revealing the level and form of violence in it, as well as knowing Whether there is a relationship between domestic violence and the conflict of emerging roles, and between domestic violence and demographic variables represented by age, work, and academic qualification, and the descriptive correlative approach was used to describe the level of emerging roles that resulted from the Corona pandemic in the Jordanian family in the northern region, and the negative effects that It was created on a random sample of (732) family members in the governorates of Irbid, Jerash and Ajlourn. The results of the study showed the presence of (19) emerging roles for Jordanian families in the North Region during the Corona pandemic, of which (16) new roles came at a high level, and three new roles came at a medium level. And that the level of the form of the marital relationship as a whole between spouses within Jordanian families in the northern region during the Corona pandemic is high, as the results showed a significant difference.